(untitled) (Progressive Agriculture, 2018)
The study was carried out to determine the effect of temperature changes on acute toxicity of pyrethroid pesticide cypermethrin in zebrafish. A two-day renewal bioassay system for 96h was conducted to find out LC50 value of cypermethrin at two temperature regimes i.e. 25°C and 30°C considering as T1 and T2, respectively. During the determination of LC50 in both temperatures, blood glucose (mg/dL) levels were measured at lower concentration (0.25 µg/L) of cypermethrin. The results of acute toxicity test at 96h LC50 values were calculated through probit analysis. It was found that 96h LC50 for T1 and T2 groups were about 2.1 and 1.4 µg/L, respectively. Significantly lower LC50 of cypermethrin at T2 compared to T1 showed that higher temperature increased the toxicity of cypermethrin. There was a significant increase (P<0.05) in blood glucose level (mg/dL) in 0.25 µg/L compared to 0 µg/L concentration of cypermethrin at both treatments. Dissolved oxygen decreased and free CO2 increased significantly (P<0.05) with increasing temperature, while the pH of the water was almost unchanged throughout the study period. The present study indicated the impact of increased temperature on pesticide toxicity in the aquatic ecosystem. Progressive Agriculture 29 (1): 64-70, 2018